An in vivo verification of the intravoxel incoherent motion effect in diffusion-weighted imaging of the abdomen - Lemke, Andreas; Laun, Frederik B.; Simon, Dirk; Stieltjes, Bram; Schad, Lothar R. (Magnetic resonance in medicine, 2010)
To investigate the vascular contribution to the measured apparent diffusion coefficient and to validate the Intra Voxel Incoherent Motion theory, the signal as a function of the b-value was measured in the healthy pancreas with and without suppression of the vascular component and under varying echo times (TE = 50, 70, and 100 msec). The perfusion fraction f and the diffusion coefficient D were extracted from the measured DW-data using the original Intra Voxel Incoherent Motion-equation and a modified version of this equation incorporating relaxation effects. First, the perfusion fraction f in the blood suppressed pancreatic tissue decreased significantly (P = 0.03), whereas the diffusion coefficient D did not change with suppression (P = 0.43). Second, the perfusion fraction f increased significantly with increasing echo time (P = 0.0025), whereas the relaxation time compensated perfusion fraction f′ showed no significant dependence on TE (P = 0.31). These results verify a vascular contribution to the diffusion weighted imaging measurement at low b values and support the Intra Voxel Incoherent Motion-theory.
Gesehen am 13.03.2023